Electrostatic Potential in High-Temperature Superconducting Cuprates: Extended Ginzburg-Landau Theory - Madhuparna Karmakar (Advances in Condensed Matter Physics)
The electrostatic potential and the associated charge distribution in the vortices of high-𝑇𝑐 superconductors involving mixed symmetry state of the order parameters have been studied. The work is carried out in the framework of an extended Ginzburg-Landau (GL) theory involving the Gorter-Casimir two-fluid model and Bardeen's extension of GL theory applied to the high-𝑇𝑐 superconductors. The properties are calculated using the material parameters relevant for the high-𝑇𝑐 cuprate YBCO.